1997
DOI: 10.1007/pl00005692
|View full text |Cite
|
Sign up to set email alerts
|

Discrete and continuous planning of hand movements and isometric force trajectories

Abstract: We have previously demonstrated that, in preparing themselves to aim voluntary impulses of isometric elbow force to unpredictable targets, subjects selected default values for amplitude and direction according the range of targets that they expected. Once a specific target appeared, subjects specified amplitude and direction through parallel processes. Amplitude was specified continuously from an average or central default; direction was specified stochastically from one of the target directions. Using the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
259
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 259 publications
(281 citation statements)
references
References 70 publications
17
259
3
1
Order By: Relevance
“…Relevant here, precues for movement extent and direction can reduce RTs additively, implying thereby that movement direction and amplitude are planned separately (Rosenbaum, 1980;Lepine et al, 1989;Bock & Arnold, 1992). This idea is also supported by disparate additional observations: speci®cation of extent and direction follows different timecourses (Ghez et al, 1997); visuomotor gains are learnt more readily and generalize more widely than directional rotations (Krakauer et al, 2000;Vindras & Viviani, 2002); learning of rotations and gains activates different cortical and subcortical networks (Krakauer et al, 2004); and, direction and extent errors vary independently (Gordon et al, 1994;Desmurget et al, 1997;Vindras & Viviani, 1998;Desmurget et al, 1999). This perspective should not be taken to imply that extent is controlled in isolation, but rather that, at certain stages of motor planning, a constellation of parameters related to the extent of movement are controlled independently from parameters related to movement direction.…”
Section: Introductionmentioning
confidence: 69%
“…Relevant here, precues for movement extent and direction can reduce RTs additively, implying thereby that movement direction and amplitude are planned separately (Rosenbaum, 1980;Lepine et al, 1989;Bock & Arnold, 1992). This idea is also supported by disparate additional observations: speci®cation of extent and direction follows different timecourses (Ghez et al, 1997); visuomotor gains are learnt more readily and generalize more widely than directional rotations (Krakauer et al, 2000;Vindras & Viviani, 2002); learning of rotations and gains activates different cortical and subcortical networks (Krakauer et al, 2004); and, direction and extent errors vary independently (Gordon et al, 1994;Desmurget et al, 1997;Vindras & Viviani, 1998;Desmurget et al, 1999). This perspective should not be taken to imply that extent is controlled in isolation, but rather that, at certain stages of motor planning, a constellation of parameters related to the extent of movement are controlled independently from parameters related to movement direction.…”
Section: Introductionmentioning
confidence: 69%
“…Using these methods it has been found that motor plans are initially established using information available from task instructions, prior experience with the task, and perception of the task layout (Ghez et al, 1997;Ghez et al, 1990;Haith et al, 2015;Hudson et al, 2007;Schutte and Spencer, 2007). Where the target is not initially specified, the initial planning state represents the information available concerning all potential targets (Cisek and Kalaska, 2002;Favilla et al, 1990;Findlay, 1982;Gallivan et al, 2015;Ghez et al, 1997;Haith et al, 2015;He and Kowler, 1989;Hudson et al, 2007;Stewart et al, 2014), and many forms for this representation have been proposed (Cisek and Kalaska, 2005;Erlhagen and Schoner, 2002;Gallivan et al, 2015;Haith et al, 2015;Kopecz and Schoner, 1995;Stewart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Where the target is not initially specified, the initial planning state represents the information available concerning all potential targets (Cisek and Kalaska, 2002;Favilla et al, 1990;Findlay, 1982;Gallivan et al, 2015;Ghez et al, 1997;Haith et al, 2015;He and Kowler, 1989;Hudson et al, 2007;Stewart et al, 2014), and many forms for this representation have been proposed (Cisek and Kalaska, 2005;Erlhagen and Schoner, 2002;Gallivan et al, 2015;Haith et al, 2015;Kopecz and Schoner, 1995;Stewart et al, 2014). Incorporation of new information into the motor plan can occur at any time prior to initiation of descending motor commands Ghez et al, 1997), and indeed there may be little or no distinction between the processes that underlie this plan updating and those responsible for feedback corrections of ongoing movements (Flanagan et al, 1993;4 Flash and Henis, 1991;Hudson et al, 2007;Nashed et al, 2014;Prablanc and Martin, 1992; van Sonderen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations